Monte Carlo calculation of Spencer-Attix and Bragg-Gray stopping-power ratios of tissue-to-air for ISO reference beta sources — an EGSnrc study. (2nd March 2021) - Palani Selvam, T.; Shrivastava, V.; Bakshi, A.K.
Abstract: On-axis Spencer-Attix and Bragg-Gray stopping power ratios of tissue-to-air are calculated for 25 radiation fields of ISO beta sources 147 Pm, 85 Kr, 90 Sr/ 90 Y and 106 Ru/ 106 Rh using the EGSnrc-based Monte Carlo code system. These values are calculated at 5 and 70 μm depths in a unit density ICRU 4-element tissue phantom, separately, for beta and photon fields using the published phase-space data at different distances with or without beam flattening filter. The study shows that the calculated values of stopping power ratios of tissue-to-air based on Spencer-Attix cavity theory are higher than the values using Bragg-Gray cavity theory for the above-mentioned sources. For example, for 90 Sr/ 90 Y source with 3 mm/4 mm PMMA filter, depending upon cavity length (l = 0.025–0.25 cm), a comparison of Spencer-Attix theory-based values with the ISO-mentioned Bragg-Gray theory-based value of 1.110 shows differences up to 1.2%. Although the study has been done for both beta and photon fields, the data corresponding to electron phase-space data are relevant as the gamma dose to the total dose is insignificant.